Building Smart Healthy Inclusive Environments for All Ages with Citizens - Willeke van Staalduinen; Carina Dantas; Joost van Hoof; Andrzej Klimczuk (Smart Objects and Technologies for Social Good. 7th EAI International Conference Proceedings, GOODTECHS 2021, Virtual Event, September 15–17, 2021, 2021)
The paper provides an introduction to the public discourse around the notion of smart healthy inclusive environments. First, the basic ideas are explained and related to citizen participation in the context of implementation of a “society for all ages” concept disseminated by the United Nations. Next, the text discusses selected initiatives of the European Commission in the field of intergenerational programming and policies as well as features of the COST Action NET4Age-Friendly: Smart Healthy Age-Friendly Environments (SHAFE). The following sections are focused on studying and discussing examples of projects and methodologies that have been aimed at: empowering facilitators of smart healthy inclusive environments, empowering citizens to deal with health emergencies, and supporting older people's voices. The conclusion covers selected recommendations for entities of public policy on ageing (ageing policy) as well as potential directions for further research.
Keywords: O18; D19; Q58; R58; 330; Age-friendly cities and communities; Citizen Participation; Inclusive Environments; Intergenerational Programmes and Policies; Smart Healthy Age-Friendly Environments (SHAFE); society for all ages